High-Bandwidth Coherent OFDM-Nyquist-TDM Transceiver With Low-Bandwidth Electronics - Younus Mandalawi; Karanveer Singh; Mohamed I. Hosni; Janosch Meier; Thomas Schneider (IEEE Access, 2023)
We present a broadband coherent orthogonal frequency-division multiplexing (OFDM) transceiver based on orthogonal sampling and low bandwidth electronic analog signal processing. Wideband superchannels, without any guardband are aggregated from low bandwidth OFDM channels in the time domain by orthogonal Nyquist sinc-pulse sequences with a rectangular bandwidth. Therefore, the method is called OFDM-Nyquist-time division multiplexing (TDM). Simulation and experimental results will be discussed for optical systems. However, with some modifications the same principle can be used for wireless or THz signals. In simulations, we show a 40 GHz bandwidth, 160 Gbps, 16-QAM, 128 OFDM x 5-Nyquist-TDM transceiver based on 4 GHz electronics for the digital-to-analog (DAC), analog-to-digital (ADC) conversion and for the digital signal processing, including Fourier transform. For the experiment, we verify the processing of a 24 GHz bandwidth, 48 Gbps QPSK, 512 OFDM x 3-Nyquist-TDM signal with a 4 GHz transmitter and receiver. Since the proposed method drastically decreases the sampling rate and bandwidth requirements for the Fourier processing, the DAC and ADC, it can be a promising alternative for future communication systems with the highest possible symbol rate.